Pengembangan Aplikasi Sistem Presensi Siswa dengan Integrasi Fitur Kehadiran Per Mata Pelajaran dan Izin Digital - Arrum Junia Budiarti; Joko Aryanto (Bulletin of Computer Science Research, 2025)
Student attendance is a crucial aspect of school administrative management; however, the conventional paper-based system implemented at SMP Negeri 1 Giritontro has several limitations, such as the risk of data loss and delays in attendance recapitulation. This study aims to develop a student attendance system application integrated with subject-based attendance features and a digital leave permission module. The software development methodology employed in this study is the Waterfall model, which includes the stages of requirements analysis, system design, implementation, and testing. The application was developed using Flutter as the frontend technology, Next.js as the backend framework, and MongoDB as the database. The results of functional testing using the Black Box Testing method indicate a 100% success rate across all normal-condition scenarios, including login functionality, subject data management, attendance recording, and digital leave submission. The system is capable of improving real-time attendance recording efficiency and providing faster access to information for students, teachers, and school administrators. Through this digitalization, student attendance management becomes more accurate, transparent, and significantly reduces administrative workload.